In vivo analysis of CRISPR-edited germinal center murine B cells - Chege Kuria, Timothy; Schneider, Andrea; Baraka, Favoured; Wanzek, Jana; Vogg, Lisa; Brey, Stefanie; Habenicht, Katharina M.; Winkler, Thomas H. (Frontiers in Immunology, 2024)
The germinal center (GC) reaction is crucial for somatic hypermutation, affinity maturation, and the selection of high-affinity B cells, all of which are hallmarks of the humoral immune response. Understanding the distinct roles of various B cell genes is essential for elucidating the selection mechanisms within the GC reaction. Traditionally, studying B cell gene function in the GC reaction involved generating knock-out mice, a highly time-consuming method that necessitates complex vectors. The advent of Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) technology has simplified the creation of knock-out mice. However, even with CRISPR, the generation of knock-out mice still faces challenges, including being time-consuming, costly, having low knock-out efficiency, and raising ethical concerns regarding animal use. To address these challenges, we developed an alternative method to traditional knock-out mouse generation. Our approach entails the ex vivo CRISPR editing of B cells from transgenic donor mice with different B cell receptor affinities followed by their adoptive transfer into recipient mice. We present a cost-effective, rapid, versatile, and adaptable CRISPR-Cas9 method for in vivo loss-of-function studies of individual murine B cell genes within the context of the GC reaction. This method provides a valuable tool for investigating the complex roles of different B cell genes in the GC selection process. As proof of concept, we validated our approach by examining the role of the pro-apoptotic gene Fas in the GC selection process. We adoptively transferred a mix of Fas knock-out (FasKO) low-affinity B cells, Fas wild-type (FasWT) low-affinity B cells, and FasWT high-affinity B cells into recipient mice. From our results, FasKO low-affinity B cells were still outcompeted by the FasWT high-affinity B cells for selection in the GC. An important observation was the accumulation of FasKO low-affinity GC B cells when compared to the FasWT low-affinity B cells, which suggested a role of Fas in the GC selection process.